Analyzing Gender-Based Financial Inclusion Disparities: A Comparative Study of Jordan and other Arab Nations - Albaddawi, Eman; Sipos, Norbert (Marketing & Menedzsment, 2025)
THE AIM OF THIS PAPER The aim of this study is to explore the financial disparities between Jordanian women and their counterparts in the Arab world. The objectives were extended to analyze country-level comparisons on a nation-to nation basis within Arab Middle Eastern countries. This study seeks to compare and evaluate educational attainment by examining the effects of education among both highly educated and non-highly educated women in Jordan, alongside their counterparts in the same region. METHODOLOGY The presented study employs the Global Findex 2021 data to examine the financial disparities between Jordanian women and their counterparts in the Arab world, using a non-parametric Mann-Whitney U test including 6317 females across 13 Arab countries. MOST IMPORTANT RESULTS Results suggested that Jordan holds a significantly distinguished position in economic empowerment despite shared cultural norms. While Jordan exhibits relative strengths in education and digital access to services, it face s significant challenges in converting these advancements into broader economic benefits and empowerment. Jordan holds a strong position compared to its counterparts in general, except for Saudi Arabia and the UAE. RECOMMENDATIONS It would be beneficial to have a context-specific policy intervention to leverage the unique position of Jordan to foster women’s economic involvement and empowerment in Jordan and